The Framework Convention on Tobacco Control: opportunities and issues El Convenio Marco para el Control del Tabaco: oportunidades y problemas - Kenneth E Warner (Instituto Nacional de Salud Pública, 2008)
The Framework Convention on Tobacco Control (FCTC), a World Health Organization sponsored global tobacco control treaty, constitutes the first major international tool with the potential to significantly reduce the global pandemic of tobacco-produced disease and death. After providing background on the prevalence of cigarette smoking and smoking attributable mortality, both at present and projected for the future, the paper then describes the FCTC and discusses its development, the barriers it has confronted, and the opportunities it offers for improving global health. Successful implementation of the provisions in the treaty could avoid literally tens of millions of premature tobacco-produced deaths over the next few decades. El Convenio Marco para el Control del Tabaco (CMCT), un tratado para el control global del tabaco patrocinado por la Organización Mundial de la Salud, constituye la primera herramienta internacional importante con el potencial de reducir significativamente la pandemia mundial de enfermedades y decesos producidos por el tabaco. Este ensayo proporciona antecedentes sobre la prevalencia de consumo de cigarrillos y sobre mortalidad atribuible a dicho consumo, tanto al presente como con proyección a futuro. Después describe el CMCT, su desarrollo, las barreras que ha confrontado y las oportunidades que ofrece para mejorar la salud global. La implementación exitosa de las disposiciones del tratado podría evitar, literalmente, decenas de millones de muertes prematuras producidas por el tabaco en las próximas décadas.